Connexin 43 (Cx43) regulates high-glucose-induced retinal endothelial cell angiogenesis and retinal neovascularization - Shi, Wen; Meng, Zhishang; Luo, Jing (Frontiers in Endocrinology, 2022)
Diabetic retinopathy (DR) is an important microvascular complication of type 1 and type 2 diabetes mellitus (DM) and a major cause of blindness. Retinal neovascularization plays a critical role in the proliferative DR. In this study, high glucose-induced connexin 43 (Cx43) expression in human retinal endothelial cells (hRECs) in a dose-dependent manner. Compared with hRECs under normal culture conditions, high-glucose (HG)-stimulated hRECs showed promoted tubule formation, increased ROS release, and elevated levels of tumor necrosis factor-alpha (TNF-α), interleukin-1β (IL-1β), vascular endothelial growth factor A (VEGFA), and intercellular adhesion molecule 1 (ICAM-1) in the culture medium. HG-induced alterations were further magnified after Cx43 overexpression, whereas partially eliminated after Cx43 knockdown. Finally, in the DR mouse model, impaired retinal structure, increased CD31 expression, and elevated mRNA levels of TNF-α, IL-1β, VEGFA, and ICAM-1 were observed; in-vivo Cx43 knockdown partially reversed these phenomena. Conclusively, Cx43 knockdown could inhibit hREC angiogenesis, therefore improving DR in the mouse model.